2020
DOI: 10.1161/circresaha.120.316951
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Platelet miR-223 Induction in Kawasaki Disease Leads to Severe Coronary Artery Pathology Through a miR-223/PDGFRβ Vascular Smooth Muscle Cell Axis

Abstract: Rationale: Kawasaki disease (KD) is an acute vasculitis of early childhood that can result in per-manent coronary artery structural damage. The etiology for this arterial vulnerability in up to 15% of KD patients is unknown. Vascular smooth muscle cell (VSMC) dedifferentiation play a key role in the pathophysiology of medial damage and aneurysm formation, recognized arterial pathology in KD. Platelet hyperreactivity is also a hallmark of KD. We recently demonstrated that uptake of platelets and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…The latter has been verified by RT-PCR to be upregulated in our previous study ( Chen Y. et al, 2018 ). Together with other studies ( Chu et al, 2017 ; Parra-Izquierdo et al, 2020 ; Zhang et al, 2020 ), our recent find ( Wang et al, 2019 ) supported that miR-223 is an important regulator of vascular endothelial cell injury in KD. Thus miR-223 may be a novel target for the treatment of KD.…”
Section: Discussionsupporting
confidence: 87%
“…The latter has been verified by RT-PCR to be upregulated in our previous study ( Chen Y. et al, 2018 ). Together with other studies ( Chu et al, 2017 ; Parra-Izquierdo et al, 2020 ; Zhang et al, 2020 ), our recent find ( Wang et al, 2019 ) supported that miR-223 is an important regulator of vascular endothelial cell injury in KD. Thus miR-223 may be a novel target for the treatment of KD.…”
Section: Discussionsupporting
confidence: 87%
“…Neutrophils and other immune cells enter the vessel wall, promoting endothelial damage and subsequent myofibroblast hyperproliferation 210 . Thrombocytopathy and endotheliopathy are shared factors in the pathogenesis of both COVID-19 and Kawasaki disease 211 . Endothelial function can remain impaired for years after Kawasaki disease resolves 212 .…”
Section: Kawasaki Diseasementioning
confidence: 99%
“…Low-dose aspirin has long been used for the treatment of Kawasaki disease, features of which have been associated with COVID-19. In addition, platelets are increasingly recognized to have a role in Kawasaki disease 211 . However, aspirin and other antiplatelet agents do not address endotheliopathy.…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%
“…For example, Zhang et al reported that without miR-223 VSMC dedifferentiation proceeds undamped resulting in medial damage, apoptosis, and MMP9 release. The elevated MMP9 levels drive the degradation of arterial wall matrix, and subsequently promoting CAA formation [80][81][82]. It is a well-known fact that SMCs senescence is also proven to enhance the formation and rupture of aneurysm as well [83,84].…”
Section: Smcs In Arterial Aneurysmmentioning
confidence: 99%